Racialized Cues and Support for Justice Reinvestment: A Mixed-Method Study of Public Opinion, Boston, 2016 - Wozniak, Kevin ([Verlag nicht ermittelbar], 2018)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. Within the past fifteen years, policymakers across the country have increasingly supported criminal justice reforms designed to reduce the scope of mass incarceration in favor of less costly, more evidence-based approaches to preventing and responding to crime. One of the primary reform efforts is the Justice Reinvestment Initiative (JRI), a public-private partnership through which state governments work to diagnose the primary drivers of their state incarceration rates, reform their sentencing policies to send fewer nonviolent offenders to prison, and reinvest the saved money that used to go into prisons into alternatives to incarceration, instead. This mixed-methods study sought to assess public opinion about the justice reinvestment paradigm of reform and to determine whether exposure to racialized and race-neutral cues affects people's willingness to allocate money into criminal justice institutions versus community-based social services in order to reduce and prevent crime.